Study of CO2 Solid Formation During Blowdown of Cryogenic CO2âCH4 Distillation Process - Shafiq, U. (Springer, 2020)
Solidification of CO2 is one of the critical issues during blowdown in the cryogenic natural gas distillation process. Cryogenic distillation process for separation of CO2 from natural gas usually works at low temperature and high pressure that produces higher purity natural gas and CO2 in the vapor-liquid phase. However, in case there is an emergency, the mixture inside distillation column is passed through blowdown valve for sudden depressurization. This rapid depressurization would cause sudden expansion of CO2 mixture resulting in a dramatic drop in the fluid temperature that could solidify CO2 and cause pipe blockage. This solidification phenomenon is not fully understood that makes the solidification of CO2 during blowdown process difficult to control. Therefore, the research study presents investigations of the thermodynamic study for the depressurization of highly pressurized vessel containing CO2âCH4 binary mixture from cryogenic conditions. Simulation is performed for 20 concentrations of CO2âCH4 mixture over different orifice size e.g. 1.00 and 1.25Â mm using BLOWDOWN software package in Aspen HYSYSÂ® V 9.0. Â© 2020, Springer Nature Singapore Pte Ltd.